The perfect family - King, Samantha (Novelist) (Kensington Publishing Corp, 2018)
Maddie Castle is broken. Ever since the tragedy that struck on her twins' tenth birthday, she's been trying to fit the pieces together, to get back to the life she led before. Maddie, her husband, Dom, and their children, Aidan and Annabel, lived in a comfortable home on a quiet street in a London suburb. Life was busy and satisfying. They were happy. Weren't they? Now, a disoriented and grieving Maddie floats like a ghost through each day, hardly sleeping, eating, or speaking. It's easier to stay locked in her own head than to torment herself by reliving what happened. And yet, the harder Maddie tries to pin down her memories, the more they slip out of reach. Is her guilt and remorse justified? Is it Maddie's fault that everything was ripped apart? Or could it be that the real terror is still to come?